11
$\begingroup$

Many years back in high school I happened to stumble upon the following property that seems to hold for any acute triangle:

enter image description here

$CD$ and $BE$ are altitudes, the arcs are semicircles with diameters $AB$ and $AC$ respectively.

The property is that $AF = AG$

Proof:

Let $H$ be the midpoint of $AB$ (and the centre of the respective semicircle) $$AG^2 = AD^2 + GD^2 = \left(AC\cdot \cos\angle A\right)^2 + GD^2$$ Since $HG = AH = \frac{AB}{2}$ is the radius of the semicircle $$GD^2 = HG^2 - HD^2 = \left(\frac{AB}{2}\right)^2 - \left(\frac{AB}{2} - AC\cdot\cos\angle A\right)^2 = \\ = AB\cdot AC\cdot \cos\angle A - \left(AC\cdot\cos\angle A\right)^2$$

which gives $$AG^2 = AB\cdot AC\cdot \cos\angle A$$

enter image description here

Analogously ($I$ is the midpoint of $AC$) $$AF^2 = AE^2 + FE^2 = \left(AB\cdot \cos\angle A\right)^2 + FE^2$$ $$FE^2 = FI^2 - EI^2 = \left(\frac{AC}{2}\right)^2 - \left(AB\cdot \cos\angle A - \frac{AC}{2}\right)^2 = \\ = AC\cdot AB\cdot \cos\angle A - \left(AB\cdot \cos\angle A\right)^2$$ which finally gives $$AF^2 = AC\cdot AB\cdot \cos\angle A$$ enter image description here

Questions:

  1. Is this a known property?
  2. Is there a better more elegant proof?
$\endgroup$
  • 1
    $\begingroup$ You can say something more: The four points where the (full) circles with diameters $\overline{AB}$ and $\overline{AC}$ meet the altitudes from $B$ and $C$, lie on a common circle about $A$. $\endgroup$ – Blue Apr 3 '18 at 16:49
  • $\begingroup$ @Blue, that's a very, very good one! Thank you. $\endgroup$ – ayorgo Apr 3 '18 at 21:54
3
$\begingroup$

HINT:

$$AF^2 = AE \cdot AC\\ AG^2 = AD \cdot AB \\ AE \cdot AC = AD \cdot AB $$

$\endgroup$
  • 1
    $\begingroup$ what a beautiful proof! $\endgroup$ – CY Aries Apr 3 '18 at 16:42
  • $\begingroup$ Brilliant indeed. Although not so trivial (to me at least). Thanks a lot. $\endgroup$ – ayorgo Apr 3 '18 at 21:41
  • $\begingroup$ @ageorge: My pleasure! A nice problem indeed! $\endgroup$ – orangeskid Apr 3 '18 at 22:32
1
$\begingroup$

This is a possibly similar proof, but here goes anyway...

Let the triangle be labelled in the usual way, so $AC=b$ and $AB=c$, and let angle $FAC=\theta$

Then $$AF=b\cos\theta$$ $$\implies FE=AF\sin\theta=b\sin\theta\cos\theta$$ $$\implies EC=FE\tan\theta=b\sin^2\theta$$ But $$EC=b-c\cos A=b\sin^2\theta$$ $$\implies b\cos^2\theta=c\cos A$$ $$\implies AF=\sqrt{bc \cos A}$$

To get $AG$ we only need to exchange $b$ and $c$, so the result follows.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.